Cardiovascular Risk Awareness and Calculated 10-Year Risk Among Female Employees at Taibah University 2019 - Qasem Surrati, Amal M.; Mohammedsaeed, Walaa; Shikieri, Ahlam B. El (Frontiers in Public Health, 2021)
Cardiovascular diseases (CVD) are the most common cause of death and disability worldwide. Knowledge about CVD and its modifiable risk factors is a vital pre-requisite to change the individuals’ health attitudes, behaviors, and lifestyle practices. Therefore, we intended to assess employee knowledge about the risk of CVD, symptoms of heart attacks, stroke and to calculate their future 10-years CVD risk. A cross-sectional study was conducted. Women aged ≥40 years who are employees of Taibah University were recruited. Those who met the inclusion criteria around 222 women were invited for the next step for the determination of CVD risk factors by using the WHO STEPS questionnaire. Also, anthropometric measurements and Biochemical measurements were done. cardiovascular disease (ASCVD) risk factors calculated using the Framingham Study Cardiovascular Disease (10-year) Risk Assessment. Data were analyzed using GraphPad Prism 7 software (GraphPad Software, CA, USA). The result showed the mean age of the study sample was 55.6 ± 9.0 years. There was an elevated percentage of obesity and risen in abdominal circumference among the women. Hypertension was a considerable chronic disease among participants where 53% suffered. According to the ASCVD risk estimator, the study participants were distributed into four groups: 63.1% at low risk, 20.2% at borderline risk, 13.5% at intermediate risk, and 3.2% at high risk. A comparison between these categories based on the CVD 10-year risk estimator indicated that there were significant variations between the low-risk group and the intermediate and high-risk groups (P= 0.02 and P= 0.001 respectively). The multivariate analysis detected factors related to CVD risk for women who have an intermediate or high risk of CVD, such as age, smoking, BMI, unhealthy diet, blood pressure measurements, and family history of CVD (P <0.05). The present study reports limited knowledge and awareness of CVD was 8.6 which is considered as low knowledge. In conclusion, the present study among the university sample in Madinah reported limited knowledge and awareness of CVD risk. These findings support the need for an educational program to enhance awareness of risk factors and the prevention of CVD.